Epigenetic and transcriptional analysis reveals a core transcriptional program conserved in clonal prostate cancer metastases. Issue 7 (11th March 2021) - Severson, Tesa M.; Zhu, Yanyun; De Marzo, Angelo M.; Jones, Tracy; Simons, Jonathan W.; Nelson, William G.; Yegnasubramanian, Srinivasan; Freedman, Matthew L.; Wessels, Lodewyk; Bergman, Andries M.; Haffner, Michael C.; Zwart, Wilbert
Abstract : The epigenomic regulation of transcriptional programs in metastatic prostate cancer is poorly understood. We studied the epigenomic landscape of prostate cancer drivers using transcriptional profiling and ChIP‐seq in four clonal metastatic tumors derived from a single prostate cancer patient. Our epigenomic analyses focused on androgen receptor (AR), which is a key oncogenic driver in prostate cancer, the AR pioneer factor FOXA1, chromatin insulator CCCTC‐Binding Factor, as well as for modified histones H3K27ac and H3K27me3. The vast majority of AR binding sites were shared among healthy prostate, primary prostate cancer, and metastatic tumor samples, signifying core AR‐driven transcriptional regulation within the prostate cell lineage. Genes associated with core AR‐binding events were significantly enriched for essential genes in prostate cancer cell proliferation. Remarkably, the metastasis‐specific active AR binding sites showed no differential transcriptional output, indicating a robust transcriptional program across metastatic samples. Combined, our data reveal a core transcriptional program in clonal metastatic prostate cancer, despite epigenomic differences in the AR cistrome. Abstract : Epigenomic and transcriptomic profiling of 4 clonal metastatic samples taken from a patient with prostate cancer during a single autopsy reveals sample‐shared/specific Androgen Receptor (AR) binding sites with enhancer activity. Sample‐shared AR sites are conserved across disease transition states, which are enriched in genes essential for prostate cancer proliferation. Remarkably, genes associated with active metastatic sample‐specific AR binding sites showed no differential transcriptional output.